Modulation of cell adhesion, proliferation and differentiation on materials designed for body implants - Bacakova, Lucie; Filova, Elena; Parizek, Martin; Ruml, Tomas; Svorcik, Vaclav (Biotechnology advances, 2011)
The interaction of cells and tissues with artificial materials designed for applications in biotechnologies and in medicine is governed by the physical and chemical properties of the material surface. There is optimal cell adhesion to moderately hydrophilic and positively charged substrates, due to the adsorption of cell adhesion-mediating molecules (e.g. vitronectin, fibronectin) in an advantageous geometrical conformation, which makes specific sites on these molecules (e.g. specific amino acid sequences) accessible to cell adhesion receptors (e.g. integrins). Highly hydrophilic surfaces prevent the adsorption of proteins, or these molecules are bound very weakly. On highly hydrophobic materials, however, proteins are adsorbed in rigid and denatured forms, hampering cell adhesion. The wettability of the material surface, particularly in synthetic polymers, can be effectively regulated by physical treatments, e.g. by irradiation with ions, plasma or UV light. The irradiation-activated material surface can be functionalized by various biomolecules and nanoparticles, and this further enhances its attractiveness for cells and its effectiveness in regulating cell functions. Another important factor for cell-material interaction is surface roughness and surface topography. Nanostructured substrates (i.e. substrates with irregularities smaller than 100nm), are generally considered to be beneficial for cell adhesion and growth, while microstructured substrates behave more controversially (e.g. they can hamper cell spreading and proliferation but they enhance cell differentiation, particularly in osteogenic cells). A factor which has been relatively less investigated, but which is essential for cell-material interaction, is material deformability. Highly soft and deformable substrates cannot resist the tractional forces generated by cells during cell adhesion, and cells are not able to attach, spread and survive on such materials. Local variation in the physical and chemical properties of the material surface can be advantageously used for constructing patterned surfaces. Micropatterned surfaces enable regionally selective cell adhesion and directed growth, which can be utilized in tissue engineering, in constructing microarrays and in biosensorics. Nanopatterned surfaces are an effective tool for manipulating the type, number, spacing and distribution of ligands for cell adhesion receptors on the material surface. As a consequence, these surfaces are able to control the size, shape, distribution and maturity of focal adhesion plaques on cells, and thus cell adhesion, proliferation, differentiation and other cell functions.
Keywords: Cell Physiological Phenomena; fyziologie buňky; povrchové vlastnosti; protézy a implantáty; testování materiálů; Materials Testing; krysa rodu Rattus; kultivované buňky; Animals; lidé; biokompatibilní materiály; Nanotechnology; Humans; zvířata; Surface Properties; Rats; myši; Prostheses and Implants; Cells, Cultured; Mice; Biocompatible Materials; nanotechnologie